Income Taxation made available - Urbano, Bartolome R. (Quezon City, 2009)
This book will be very useful to students of accountancy, management, finance and business, as it explains the principle behind Philippine income tax law in layman's terms. To facilitate learning, cases are presented which illustrate how such principles are applied in real life. Step-by-step computations and solutions to problems are shown to assure clarity and understanding.
Keywords: Income Tax